Propriedades térmica, oxidativa e uidodinâmica de biodiesels obtidos a partir de misturas quaternárias de óleos vegetais - Freire, Lécia Maria da Silva (2012)
The properties of oils and biodiesel produced from these raw materials are strongly in uenced by the composition of individual fatty acids and esters that compose them. Esters derived from saturated fatty acids have a high point of fog, high viscosity and this fact can obstruct the injectors of the engines. Esters derived from unsaturated fatty acids are less viscous, however, more susceptible to oxidation. The aim of this study is to propose a methodology that improves the thermal and oxidative stability, as well as the ow properties of biodiesel without the addition of antioxidants and antifreeze. Quaternary mixtures of vegetable oils were prepared (soybean-OSJ, cotton -OAG, jatropha-OPM, and babassu-OBB), and then transesterification of these mixtures were carried out to obtaining biodiesels. Oils and mixtures were studied by thermogravimetry (TGA) and samples which present a higher thermal stability were: OBB (335,2 oC), M4O (329,6 oC) e BM2 (204,7 oC). The oxidative induction time (PI) of oils and mixtures was measured through the PDSC, Petro-OXY and Rancimat. Among the oils with the highest OIT were the OBB and the smallest OAG, and among the mixtures that had the best and the worst OIT were M4O and M1O, respectively. The results above were corroborated by the iodine index and unsaturation content. In respect to the ow properties, all samples showed Newtonian behavior, so the M40 and OBB present the lower absolute and kinematic viscosity and higher cloud point and pour point. The synthesis of biodiesels was performed using an oil:methanol ratio, 1:3.36 moles. Among the syntheses carried out with five quaternary mixtures and four of them presented conversion in ester above 99% w/w. In General, OIT found to the biodiesels study were better than those presented in the literature for biodiesels obtained with the pure oil.